Transcriptomic Response in the Heart and Kidney to Different Types of Antihypertensive Drug Administration. Issue 2 (9th December 2021) - Takeuchi, Fumihiko; Liang, Yi-Qiang; Isono, Masato; Ang, Mia Yang; Mori, Kotaro; Kato, Norihiro
Abstract : Supplemental Digital Content is available in the text. Abstract : Certain classes of antihypertensive drug may exert specific, blood pressure (BP)-independent protective effects on end-organ damages such as left ventricular hypertrophy, although the overall evidence has not been definitive in clinical trials. To unravel antihypertensive drug-induced gene expression changes that are potentially related to the amelioration of end-organ damages, we performed in vivo phenotypic evaluation and transcriptomic analysis on the heart and the kidney, with administration of antihypertensive drugs to two inbred strains (ie, hypertensive and normotensive) of rats. We chose 6 antihypertensive classes: enalapril (angiotensin-converting enzyme inhibitor), candesartan (angiotensin receptor blocker), hydrochlorothiazide (diuretics), amlodipine (calcium-channel blocker), carvedilol (vasodilating β-blocker), and hydralazine. In the tested rat strains, 4 of 6 drugs, including 2 renin-angiotensin system inhibitors, were effective for BP lowering, whereas the remaining 2 drugs were not. Besides BP lowering, there appeared to be some interdrug heterogeneity in phenotypic changes, such as suppressed body weight gain and body weight-adjusted heart weight reduction. For the transcriptomic response, a considerable number of genes showed prominent mRNA expression changes either in a BP-dependent or BP-independent manner with substantial diversity between the target organs. Noticeable changes of mRNA expression were induced particularly by renin-angiotensin system blockade, for example, for genes in the natriuretic peptide system ( Nppb and Corin ) in the heart and for those in the renin-angiotensin system/kallikrein-kinin system ( Ren and rat Klk1 paralogs) and those related to calcium ion binding ( Calb1 and Slc8a1 ) in the kidney. The research resources constructed here will help corroborate occasionally inconclusive evidence in clinical settings.